Design of patent foramen ovale closure trials: the importance of patient-reported outcomes. (September 2011) - Carroll, John D; Patrick-Lake, Bray
Clinical trials assessing the safety and comparative effectiveness of catheter-delivered device closure of patent foramen ovale are active in multiple common disorders including migraine headaches and cryptogenic stroke. Trials began with multiple single-center studies using historical controls, a few prospective studies and, more recently, randomized clinical trials sponsored by the medical device industry in order to gain regulatory approval. While numerous problems have frustrated investigators and sponsors of identifying the appropriate target population and suboptimally performing devices, during the current period of redesigning future trials there has been a new focus on incorporating better measures of outcomes. The need for, and value of, patient-report outcomes are discussed in this article. While subjective symptoms have been used as clinical end points in some studies the broader application of patient-report outcomes is necessary to understand treatment differences more comprehensively and gather data that will assist in clinical decision making and the determination of patient preferences. These issues are discussed in the context of new clinical trials but also in the post-approval period when longitudinal outcomes must be studied over a prolonged period of time with these chronic disorders with disabling manifestations, high personal socioeconomic burdens, and large societal costs.